Immunological Characteristics of Patients Receiving Ultra-Short Treatment for Chronic Hepatitis C - Madsen, Lone Wulff; Christensen, Peer Brehm; Øvrehus, Anne; Bryde, Dorthe Marie Sjødahl; Holm, Dorte Kinggaard; Lillevang, Søren Thue; Nielsen, Christian (Frontiers in Cellular and Infection Microbiology, 2022)
Reducing the treatment duration for chronic hepatitis C could be an important tool in the effort to reach the elimination goals set by the World Health Organization. The current challenge is to predict the target group who will achieve sustained virological response at week 12 (SVR12) with shorter treatment duration. The aim of this exploratory study was to characterize immune subsets with focus on inhibitory receptors in patients who experienced SVR12 or virological relapse following four weeks treatment with glecaprevir/pibrentasvir with or without ribavirin. A total of 32 patients were included in this study of whom 21 achieved SVR12 and 11 had virological relapse. All available samples at baseline (n = 31) and end of treatment (EOT) (n = 30) were processed for flow cytometric analysis in order to measure the expression of PD-1, 2B4, BY55, CTLA-4, TIM-3 and LAG-3 on 12 distinct T cell subsets. At baseline, patients with SVR12 (n=21) had numerically lower frequencies of inhibitory receptors for 83% (60/72) of the investigated T-cell subtypes. The most significant difference observed between the two groups was a lower frequency of stem cell-like memory T-cells CD4+PD1+ in the SVR group (p = 0.007). Furthermore, we observed a significant positive correlation between baseline viral load and the expression of PD-1 on the total CD8+ T-cells and effector memory T-cells CD4+ and CD8+ for patients with virological relapse. This study suggests a measurable immunologic phenotype at baseline of patients achieving SVR12 after short treatment compared to patients with virological relapse.